2015
DOI: 10.1103/physrevb.92.085140
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved Landau level spectroscopy of the topological Dirac cone of bulk-typeSb2Te3(0001): Potential fluctuations and quasiparticle lifetime

Abstract: Using low temperature scanning tunneling spectroscopy, we probe the Landau levels of the topologically protected state of Sb2Te3(0001) after in-situ cleavage of a single crystal. Landau levels are visible for magnetic fields B ≥ 2 T at energies, which confirm the Dirac type dispersion including the zeroth Landau level. We find different Dirac velocities for the lower and the upper part of the Dirac cone in reasonable agreement with previous density functional theory data. The Dirac point deduced from the zerot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 84 publications
(122 reference statements)
4
24
1
Order By: Relevance
“…2(b) revealing that, while electron-and hole-like branches of the Dirac cone have similar slopes in regions where the Dirac point is well above the Fermi (blue lines), a kink signaling the breaking of the electron-hole symmetry becomes evident once the Dirac point is closer to the Fermi (red line). Note that electron-hole asymmetries have been previously reported in the Dirac spectrum of TIs [14,17]. Their existence is not surprising and can be traced back to density functional theory data [18].…”
supporting
confidence: 53%
“…2(b) revealing that, while electron-and hole-like branches of the Dirac cone have similar slopes in regions where the Dirac point is well above the Fermi (blue lines), a kink signaling the breaking of the electron-hole symmetry becomes evident once the Dirac point is closer to the Fermi (red line). Note that electron-hole asymmetries have been previously reported in the Dirac spectrum of TIs [14,17]. Their existence is not surprising and can be traced back to density functional theory data [18].…”
supporting
confidence: 53%
“…Figure 6(i) shows STM data of in-situ cleaved Sb 2 Te 3 (0001) featuring a few defects that have been identified previously by comparison with DFT calculations as Sb substitutional in the upper Te layer (Sb Te , bright) and vacancies in the Sb layer directly below the surface (Vac Sb , dark) [69]. We find a defect density of 4·10 12 /cm 2 with all apparent defects attributed to the upper QL [49]. Figure 6(j)-(k) show Landau level spectra recorded at two different locations of the sample.…”
Section: Disorder Characterizationmentioning
confidence: 54%
“…Moreover, LL0 appears at the same energy as the minimum in dI/dV (V ) curves at B = 0 T. Finally, LL0 deviates by ∼ 40 meV between the two probed areas indicating the potential fluctuations. We found that the deduced LL0 energy correlates with the local density of defects visible in the STM data (not shown) [49]. Weak 3DTIs have initially barely been studied due to the wrong conjecture that they are unstable with respect to most type of perturbations [24].…”
Section: Disorder Characterizationmentioning
confidence: 72%
“…As the distance between adjacent Landau levels depends on the effective electron mass, LLS is usually restricted to materials with LL spacings larger than the life‐time broadening, i.e. semiconductors with low electron masses or Dirac‐like materials,, such as graphene or the surface states of topological insulators (TI). The latter exhibit a linear dispersion relation that results in a square root dependence of LL energies: EnEnormalD=sgntrue(ntrue)υD2e|n|B0.0ex0.0ex0.3em=sgntrue(ntrue)υD|kn|, where n = 0, ±1 … is the LL index, B=μ0H the magnetic flux density, and υnormalD the Dirac velocity.…”
mentioning
confidence: 99%
“…Here, we present an LLS investigation of the three‐dimensional topological insulator Sb 2 Te 3 . Sb 2 Te 3 was chosen because – in contrast to its sister compounds Bi 2 Te 3 and Bi 2 Se 3 – it gives access to both positive and negative LL, which are energetically symmetrically located above and below the Dirac point, respectively. Our data show that the width of the zeroth LL located at the Dirac energy is maximal and that the LL width monotonously decreases with increasing absolute value of the LL index, |n|, inconsistent with conventional scattering mechanism.…”
mentioning
confidence: 99%